Functional mitral regurgitation in advanced heart failure. (4th February 2022) - Dias Ferreira Reis, JP; Bras, P; Goncalves, A; Pereira Da Silva, T; Soares, R; Timoteo, AT; Galrinho, A; Branco, L; Ferreira, R
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Moderate-to-severe functional mitral regurgitation (fMR) is present in about one-third of patients with heart failure (HF) with reduced left ventricular (LV) ejection fraction (HFrEF) and contributes to progression of the symptoms of HF and is and independent predictor of worse clinical outcomes. Objective: To characterize the population of advanced HF patients with severe fMR and assess its prognostic impact. Methods: Prospective evaluation of adult patients with advanced HFrEF were referred to our Institution for evaluation with HF team and possible indication for urgent heart transplantation (HT) or MCS. Patients were followed up for 1 year for the primary endpoint of cardiac death and HT. Severe fMR was defined by an EROA ≥ 20 mm2 and/or a regurgitant volume (RVol) ≥ 30 mL either taken from TTE or TOE. A survival analysis was performed to evaluate the prognostic impact of fMR and survival curves were compared using the log-rank test. Results: A total of 450 HFrEF patients (mean age of 56 ± 12 years, 80% male, mean LVEF of 29 ± 4%) of which 14.4% had severe fMR, with a mean EROA of 29.2 ± 3.1 mm2 and a mean RVol of 43.6 ± 4.7 mL. Thirty patients (6.7%) met the primary endpoint. Patients with severe fMR were more likely to be female (69.2% vs 81.5%, p = 0.026) and to have atrial fibrillation (27.0% vs 14.1%, p = 0.028), had a higher NT-proBNP value (3625.8 ± 496.9 vs 1940 ± 212.4 pg/mL, p = 0.001), a lower LVEF (25.9 ± 6.8 vs 29.0 ± 6.7, p = 0.001), more dilated LV (LV end-diastolic diameter: 72.8 ± 13.3 vs 66.9 ± 9.0 P = 0.036), a lower HFSS value (8.1 ± 1.0 vs 8.6 ± 1.0). There was no difference regarding HF etiology, NYHA class or cardiopulmonary fitness (pVO2: 16.6 ± 5.6 vs 16.5 ± 6.3 ml/kg/min, p = 0.19; VE/VCO2 slope: 35.4 ± 9.9 vs 34.0 ± 9.7, p = 0.328). EROA was an independent predictor of the primary outcome (OR 1.23, 95% CI 1.08-1.54, p = 0.039) and patients with severe fMR had a lower survival free of events during the first follow-up year (log-rank p = 0.012). Conclusion: Severe fMR was associated with worse clinical outcomes in advanced HF population.